Cover Feature: Polyhydrido Copper Nanoclusters with a Hollow Icosahedral Core: [Cu30H18E2P(OR)212] (E=S or Se; R=nPr, iPr or iBu) (Chem. Eur. J. 46/2020). Issue 46 (3rd August 2020) - Barik, Subrat Kumar; Huo, Shou‐Chih; Wu, Chun‐Yen; Chiu, Tzu‐Hao; Liao, Jian‐Hong; Wang, Xiaoping; Kahlal, Samia; Saillard, Jean‐Yves; Liu, C. W.
Abstract : The structurally precise polyhydrido copper nanocluster (NC) [Cu30 H18 S2 P(O n Pr)2 12 ] which contains an unprecedented inner hollow Cu12 icosahedral core has been fully characterized by single‐crystal neutron diffraction; while Ag12 and Au12 inner hollow icosahedra encircled within Ag44 and Au32 NCs have been reported by Bigioni and Wang in 2013 and 2019, respectively. Pd doping on the Cu30 NC led to the isolation of Pd−Cu bimetallic NCs, which exhibit a linear [(PdH2 ) 2− ]‐centered icosahedral core. More information can be found in the Full Paper by J.‐Y. Saillard, C. W. Liu, et al. on page 10471 .